Health-economic burden attributable to novel serotypes in candidate 24- and 31-valent pneumococcal conjugate vaccines - King, Laura M.; Lewnard, Joseph A. (Vaccine, 2024)
Introduction: Next-generation pneumococcal vaccines currently in clinical trials include 24- and 31-valent pneumococcal conjugate vaccines (PCV24, PCV31), which aim to prevent upper-respiratory carriage and disease involving the targeted serotypes. We aimed to estimate the comprehensive health-economic burden associated with acute respiratory infections (ARIs) and invasive pneumococcal disease (IPD) attributable to PCV24- and PCV31-additional (non-PCV20) serotypes in the United States. Material and methods: We multiplied all-cause incidence rate estimates for acute otitis media (AOM), sinusitis, and non-bacteremic pneumonia by estimates of the proportions of each of these conditions attributable to pneumococci and the proportions of pneumococcal infections involving PCV24- and PCV31-additional serotypes. We estimated serotype-specific IPD incidence rates using US Active Bacterial Core surveillance data. We accounted for direct medical and non-medical costs associated with each condition to estimate resulting health-economic burden. Non-medical costs included missed work and lost quality-adjusted life years due to death and disability. Results: The health-economic burden of PCV24-additional serotypes totaled $1.3 ($1.1–1.7) billion annually in medical and non-medical costs, comprised of $0.9 ($0.7–1.2) billion due to ARIs and $0.4 ($0.3–0.5) billion due to IPD. For PCV31-additional serotypes, medical and non-medical costs totaled $7.5 ($6.6–8.6) billion annually, with $5.5 ($4.7–6.6) billion due to ARIs and $1.9 ($1.8–2.1) billion due to IPD. The largest single driver of costs was non-bacteremic pneumonia, particularly in adults aged 50–64 and ≥65 years. Conclusions: Additional serotypes in PCV24 and PCV31, especially those included in PCV31, account for substantial health-economic burden in the United States. •New pneumococcal conjugate vaccines targeting 24/31 serotypes are currently in clinical trials.•Non-PCV20 serotypes in PCV24 account for burdens of $1.3 billion USD annually.•Non-PCV20 serotypes in PCV31 account for burdens of $7.5 billion each year.•Costs were driven by non-bacteremic pneumonia, particularly in adults ≥50 years.